Nomination of Protestantism in French Royal Decrees of the 16th Century (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-39-49The paper analyzes how Protestantism was denoted in French royal edicts of the 16th century. The social tension of the period of religious conflicts was unavoidably reflected in the Middle French language. Our task is to trace how it affected the language of law; in particular, what vocabulary was used in legal texts to denote the Reformation and whether it corresponded to the linguistic traditions of formulating legal issues that had developed by that time.  We divide the royal statutes into two groups, representing two different legal and language policies applied to Protestantism. The first group includes royal edicts from the first half of the century, where derogatory vocabulary is used to denote the Reformation. The second group contains documents from the last third of the 16th century. They introduce newer, neutral terms for Protestantism, diametrically opposed to the earlier pejorative designations.Key words: Reformation, 16th century, legal discourse, royal decree, law, canon law, nomination.